factorise polynomial

Asked by  | 12th May, 2008, 11:06: AM

Expert Answer:

Let x3 -3x2 - 9x - 5 = 0

If we put x = -1 it satisfies the equation as we get 0. Which means (x + 1) is one of the factors of the given equation.

Now if we divide the given equation by (x + 1) we get (x2 - 4x - 5) So the given equation becomes :

= (x + 1) (x2 - 4x - 5)

= (x + 1) (x - 5) (x + 1)

= (x - 5) (x + 1)2

Answered by  | 13th May, 2008, 12:36: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.